2008
DOI: 10.1159/000139130
|View full text |Cite
|
Sign up to set email alerts
|

HTLV-I Production Based on Activation of Integrin/Ligand Signaling in HTLV-I-Infected T Cell Lines Derived from HAM/TSP Patients

Abstract: Objective: Activity of integrin/ligand signaling leading to activation of small GTPases might regulate the efficiency of cell-to-cell spread of human T lymphotropic virus type I (HTLV-I) through the virological synapse. We compared both activity of small GTPases and involvement of integrin/ligand signaling in extracellular release of HTLV-I virions between each three HTLV-I-infected T cell lines derived from HTLV-I-associated myelopathy/tropical spastic paraparesis (HAM/TSP) patients and from other origins as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 57 publications
(28 reference statements)
0
15
0
Order By: Relevance
“…Previously, we reported that activation of integrin/ligand followed by activation of small GTPases, such as Rac and Cdc42, can contribute to efficient intercellular transmission of HTLV-I. 6 Another small GTPase, Rap1, is a potent stimulator of integrins, such as aLb2 and very late antigen 4, and facilitates inside-out signaling. 8,13 Hence, CXCR4 signaling upstream of Rap1 could also contribute to efficient intercellular transmission of HTLV-I.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we reported that activation of integrin/ligand followed by activation of small GTPases, such as Rac and Cdc42, can contribute to efficient intercellular transmission of HTLV-I. 6 Another small GTPase, Rap1, is a potent stimulator of integrins, such as aLb2 and very late antigen 4, and facilitates inside-out signaling. 8,13 Hence, CXCR4 signaling upstream of Rap1 could also contribute to efficient intercellular transmission of HTLV-I.…”
Section: Discussionmentioning
confidence: 99%
“…However, the increased proliferation of HTLV‐I‐infected cells seems to play a highly important role in this effect, and it can be speculated that efficient intercellular transmission of HTLV‐I is also partially responsible. Indeed, we previously reported that HTLV‐I production by HAM/TSP patient‐derived HTLV‐I‐infected T‐cell lines, in which Rac and Cdc42 are activated, is downregulated by blockade of integrin/ligand interactions, suggesting that the extracellular release of HTLV‐I from these HTLV‐I‐infected T‐cell lines depends on the reorganization status of the cytoskeleton after activation of integrin/ligand signaling. Therefore, HAM/TSP‐derived HTLV‐I‐infected T‐cell lines might have the activity of efficient intercellular transmission of HTLV‐I.…”
Section: Discussionmentioning
confidence: 99%
“…Interleukin‐2 (IL‐2)‐dependent HTLV‐I‐infected T‐cell line derived from the cerebrospinal fluid of an HAM/TSP patient (HCT‐5) and IL‐2‐independent HTLV‐I‐infected T‐cell line derived from an HTLV‐I carrier (TL‐Su) were used in the present study …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the coculture of SGECs with HTLV-I-producing T cells, HCT-5 cells (which are derived from the cerebrospinal fluid cells of patients with HAM [14]), were cultured with SGECs for the designated period of time in defined keratinocyte-SFM culture medium. As a control toward HCT-5, the non-HTLV-I-infected T cell line Jurkat was cultured in RPMI 1640 medium with 10% fetal bovine serum.…”
Section: Methodsmentioning
confidence: 99%